Heterogenous life expectancy, adverse selection, and retirement behaviour - Matthias Heidler; Bernd Raffelhüschen; Arne Leifels (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2006)
This article surveys the literature on selection effects in retirement behavior. More specifically, we consider early retirement schemes with actuarially fair adjustments based on average life expectancy. To this end, we recapitulate the theoretical literature on selection effects and resulting optimal benefit rule design. Yet, the emphasis is on the results of the heterogeneous empirical literature. Indeed, there is evidence of individuals incorporating private information about their life expectancy into retirement decisions. But other determinants of retirement choice turn out significant, too, e.g. health, changes in family structure, or sheer affordability. The literature does not provide clear results concerning the relative magnitude of these effects.
Keywords: H55; J32; D82; 330; Flexible Altersgrenze; Arbeitsangebot; Sterblichkeit; Adverse Selection; Schätzung; Theorie; Deutschland